THEORY OF FORMATION OF STRATEGIC COMPETENCE IN COMMUNICATION ACTIVITIES - Boltabayeva Dilshoda Bakhrommirza kizi (World Scientific Research Journal, 2025)
Abstract. This article analyzes the theoretical foundations of the formation of strategic competence in communicative activity. In the processes of language learning and communication, not only grammatical or lexical knowledge is important, but also strategic competence - that is, the skills of choosing and applying the right strategies to achieve the goal of communication. The author considers the stages of formation of strategic competence, factors and methodological approaches that influence it. The role of active cooperation and dialogue between the teacher and the student in the development of this competence is also revealed. Through theoretical analysis, effective directions for the development of strategic competence have been identified.